2019
DOI: 10.1111/dom.13677
|View full text |Cite
|
Sign up to set email alerts
|

Lower rates of cardiovascular events and mortality associated with liraglutide use in patients treated with basal insulin: A DEVOTE subanalysis (DEVOTE 10)

Abstract: Aim To compare the associations between concomitant liraglutide use versus no liraglutide use and the risk of major adverse cardiovascular events (MACE) and all‐cause mortality among patients receiving basal insulin (either insulin degludec [degludec] or insulin glargine 100 units/mL [glargine U100]) in the Trial Comparing Cardiovascular Safety of Insulin Degludec versus Insulin Glargine in Patients with Type 2 Diabetes at High Risk of Cardiovascular Events (DEVOTE). Materials and Methods Patients with type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
2
9
1
Order By: Relevance
“…A recent subgroup analysis of the DEVOTE trial showed a reduced risk of MACE in patients using liraglutide in combination with basal insulin compared with patients using basal insulin without liraglutide, over a median follow‐up of 2 years . Adding further support to our results, this analysis also showed a non‐significant trend for a reduced risk of severe hypoglycaemia, and slightly lower mean bolus insulin dose in patients with concomitant liraglutide use …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A recent subgroup analysis of the DEVOTE trial showed a reduced risk of MACE in patients using liraglutide in combination with basal insulin compared with patients using basal insulin without liraglutide, over a median follow‐up of 2 years . Adding further support to our results, this analysis also showed a non‐significant trend for a reduced risk of severe hypoglycaemia, and slightly lower mean bolus insulin dose in patients with concomitant liraglutide use …”
Section: Discussionsupporting
confidence: 83%
“…13 Adding further support to our results, this analysis also showed a non-significant trend for a reduced risk of severe hypoglycaemia, and slightly lower mean bolus insulin dose in patients with concomitant liraglutide use. 13…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…22,23 Degludec demonstrated non-inferiority to IGlar U100 22 and liraglutide in reducing the risk of major adverse cardiovascular events compared with placebo. 23 Furthermore, post hoc sub-analyses of the DEVOTE 24 and DUAL programme 25 were in agreement with these findings, suggesting that cardiovascular safety was preserved.…”
Section: Apy (Insulin Glargine 100 Units/ml [Iglar U100] + Insulin Asmentioning
confidence: 62%
“…DEVOTE demonstrated that degludec was non-inferior to glargine with respect to the incidence of major CV events (MACE) in participants with T2D at high risk for CV events (n = 7637) [33]. A post hoc analysis of participants in DEVOTE, which compared outcomes between participants concomitantly treated with liraglutide with those who had no liraglutide use, found that participants treated with degludec or IGlar U100 with liraglutide had significantly fewer MACE compared with participants in the degludec/IGlar U100 without liraglutide group (hazard ratio [HR] 0.62, 95% CI 0.41; 0.92; p = 0.02 [71]). This observation suggested that liraglutide might have CV benefits for people treating their T2D with basal insulin.…”
Section: Cardiovascular (Cv) Safetymentioning
confidence: 99%